Pregnant in Foster Care: Prenatal Care, Abortion, and the Consequences for Foster Families - Moore, Katherine (Columbia Journal of Gender and Law, 2012)
Girls in foster care get pregnant. A lot.’ For example, in 2005 the New York City Office of the Public Advocate estimated that as many as “[o]ne in six young women in foster care in New York City are pregnant or are already mothers…” When a teenage girl gets pregnant, there is always a complex set of issues and challenges that she will face: whether or not she will continue the pregnancy, what medical services are available to her if she decides to have the child, what abortion services are available to her if she does not, who will retain custody of the baby, whether she will give the baby up for adoption. For a pregnant teen in foster care, these issues are amplified by the child welfare system, where there are many more actors in play than just the pregnant girl, her parents, and the father of her child. The foster parents, the biological parents, and the state each play a substantial role in determining how the pregnant foster girl manages her pregnancy and the resources available to her, yet at the same time, the existing legislation and policies guiding these actors are inadequate for addressing her needs and often hinder her ability to exercise her rights.